2012
DOI: 10.1038/ncomms1739
|View full text |Cite
|
Sign up to set email alerts
|

SUMO modification of the neuroprotective protein TDP1 facilitates chromosomal single-strand break repair

Abstract: Breaking and sealing one strand of DNA is an inherent feature of chromosome metabolism to overcome torsional barriers. Failure to reseal broken DNA strands results in protein-linked DNA breaks, causing neurodegeneration in humans. This is typified by defects in tyrosyl DNA phosphodiesterase 1 (TDP1), which removes stalled topoisomerase 1 peptides from DNA termini. Here we show that TDP1 is a substrate for modification by the small ubiquitin-like modifier SUMO. We purify SUMOylated TDP1 from mammalian cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 55 publications
3
77
0
Order By: Relevance
“…It has been suggested that the TDP1 N-terminal domain mediates interactions with DNA repair proteins (28, 4850). Deletion of the N-terminal domain of TDP1 produced the catalytically active TDP1-ΔN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the TDP1 N-terminal domain mediates interactions with DNA repair proteins (28, 4850). Deletion of the N-terminal domain of TDP1 produced the catalytically active TDP1-ΔN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A) promotes DNA repair and TDP1 accumulation at Top1cc-induced and UV-laser-induced DNA damage sites [105]. SUMOylation is catalyzed in a three-step process by E1, E2, and E3 enzymes followed by desumoylation by proteases specifically recognizing SUMO conjugates [106,107].…”
Section: Tyrosyl-dna Phosphodiesterase 1 (Tdp1)mentioning
confidence: 99%
“…Upon exposure to H 2 O 2 , 1000-fold more SSBs are induced in nDNA as compared with DSBs (Caldecott 2008). SSBs can also arise as a result of erroneous or abortive activity of DNA topoisomerase 1 (Hudson et al 2012), which is present in mitochondria, where it participates in transcription and replication (Zhang et al 2001). 5 0 -AMPSSBs, in which AMP is covalently linked to a 5 0 -phosphate through a pyrophosphate bond, arise from abortive DNA-ligase activity at existing SSBs and are processed by aprataxin (Ahel et al 2006), another mitochondrial protein (Sykora et al 2011).…”
Section: Single-strand Break Repair (Ssbr)mentioning
confidence: 99%